Electron energy loss spectroscopy determination of Ti oxidation state at the (001) LaAIO3/SrTiO3 interface as a function of LaAIO3 growth conditions - Maurice, J.-L; Herranz, G; Colliex, C; Devos, I; Carrétéro, C; Barthélémy, A; Bouzehouane, K; Fusil, S; Imhoff, D; Jacquet, É; Jomard, F; Ballutaud, D; et al. (Europhysics letters, 2008)
After the epitaxy of LaAlO3 on a TiO2-terminated {100} surface of SrTiO3, a high-mobility electron gas may appear, which has been the object of numerous works over the last four years. Its origin is a subject of debate between the interface polarity and unintended doping. Here we use electron energy loss “spectrum images”, recorded in cross-section in a scanning transmission electron microscope, to analyse the Ti3+ ratio, characteristic of extra electrons. We find an interface concentration of Ti3+ that depends on growth conditions.